Unemployment in Kazakhstan and its dynamics (Journal of Economic Research & Business Administration, 2016)
Unemployment is serious problem that government faces. Unemployment rates of any country pose a complicated puzzle. The paper discusses the basic concepts of unemployment in the economic system, describes the basic terms and definitions are given and analyzed the causes and consequences of unemployment. The article presents statistical data, as well as highlighted the problem of development of Kazakhstan’s labor mar ket influences on unemployment, social and economic consequences of unemployment. Also there is a statistical review of the labor market of Kazakhstan at work.
Keywords: unemployment; employment; economically active population; GDP; productivity.